2022
DOI: 10.1007/s40145-022-0625-z
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the melting point and phase stability of rare-earth oxides to facilitate their crystal growth from the melt

Abstract: The challenge of growing rare-earth (RE) sesquioxide crystals can be overcome by tailoring their structural stability and melting point via composition engineering. This work contributes to the advancement of the field of crystal growth of high-entropy oxides. A compound with only small REs (Lu,Y,Ho,Yb,Er)2O3 maintains a cubic C-type structure upon cooling from the melt, as observed via in-situ high-temperature neutron diffraction on aerodynamically levitated samples. On the other hand, a compound with a mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The melting point of Gd 2 O 3 is reported in the range of 2392–2445 °C while composition 1 solidifies ∼2350 °C. This is in agreement with previous work that demonstrated that the melting point of RE 2 O 3 can be suppressed in high-entropy compositions with similar AIR . The B- to H-type transition temperature of Gd 2 O 3 is reported in the range of 2170–2195 °C, , while composition 1 had this transition at ∼2150 °C, which is close to the lower end of this range.…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The melting point of Gd 2 O 3 is reported in the range of 2392–2445 °C while composition 1 solidifies ∼2350 °C. This is in agreement with previous work that demonstrated that the melting point of RE 2 O 3 can be suppressed in high-entropy compositions with similar AIR . The B- to H-type transition temperature of Gd 2 O 3 is reported in the range of 2170–2195 °C, , while composition 1 had this transition at ∼2150 °C, which is close to the lower end of this range.…”
Section: Results and Discussionsupporting
confidence: 92%
“…This is in agreement with previous work that demonstrated that the melting point of RE 2 O 3 can be suppressed in high-entropy compositions with similar AIR. 41 The B-to H-type transition temperature of Gd 2 O 3 is reported in the range of 2170−2195 °C, 36,39 while composition 1 had this transition at ∼2150 °C, which is close to the lower end of this range. Therefore, the polymorphic behavior of single-RE 2 O 3 can be used to predict the type of phase transformations that may occur in high-entropy RE 2 O 3 .…”
Section: Phase Evolution Of Composition 1 (Luyhondla) 2 Omentioning
confidence: 86%
“…Measurements up to temperatures close to the melting point of these compounds would be advisable to capture the full dependence of the structural behavior on temperature. Maximum experimental temperatures around 2100°C would be required since the melting points of single‐RE RE 4 Al 2 O 9 are in the range of 1950–2040°C, 4 and the melting points of high‐entropy oxides is usually lower or similar to their single‐cation analogous oxides 24,41,42 . Such extreme temperature measurements require careful treatment to avoid reactions between the sample and sample holder.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we demonstrate crystal growth of high‐entropy RE 4 Al 2 O 9 for the first time, contributing to the emerging field of crystal growth of high‐entropy oxides 24–34 . The phase formation and optical quality of crystals containing five REs, including Lu, Yb, Er, Y, Ho, Dy, Tb, Gd, Eu, Sm, Nd, and La were evaluated.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation